Optimization of electron beam-deposited silver nanoparticles on zinc oxide for maximally surface enhanced Raman spectroscopy. Issue 2 (9th December 2020) - Cook, Andrew L.; Haycook, Christopher P.; Locke, Andrea K.; Mu, Richard R.; Giorgio, Todd D.
Abstract : Fabrication and anneal parameters of electron beam-deposited silver nanoparticles can be optimized to maximize surface-enhanced Raman spectroscopy of dilute analytes. Abstract : Surface enhanced Raman spectroscopy enables robust, rapid analysis on highly dilute samples. To be useful, the technique needs sensing substrates that will enhance intrinsically weak Raman signals of trace analytes. In particular, three-dimensional substrates such as zinc oxide nanowires decorated with electron-beam deposited silver nanoparticles are easily fabricated and serve the dual need of structural stability and detection sensitivity. However, little has been done to optimize electron beam-deposited silver nanoparticles for maximal surface enhancement in the unique dielectric environment of the zinc oxide substrate. Herein, fabrication and anneal parameters of electron beam-deposited silver nanoparticles were examined for the purpose of maximizing surface enhancement. Specifically, this work explored the effect of changing film thickness, deposition rate, anneal temperature, and anneal time on the surface plasmon resonance of Ag nanoparticles. In this study, multiple sets of fabrication and annealing parameters were discovered that optimized surface plasmon resonance for maximal enhancement to Raman signals acquired with a 532 nm laser. This work represents the first characterization of the fabrication and annealing parameters for electron beam-deposited silver nanoparticles on zinc oxide.